2023
DOI: 10.1200/jco.22.01423
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Mechanisms to Anti–Epidermal Growth Factor Receptor Therapy in RAS/RAF Wild-Type Colorectal Cancer Vary by Regimen and Line of Therapy

Abstract: PURPOSE Acquired resistance to anti-EGFR therapy (EGFRi) in CRC has previously been explained by the model of acquiring new mutations in KRAS/NRAS/EGFR, among other MAPK-pathway members. However, this was primarily based on single-agent EGFRi trials and little is known about the resistance mechanisms of EGFRi combined with effective cytotoxic chemotherapy in previously untreated patients. METHODS We analyzed paired plasma samples from RAS/BRAF/EGFR wild-type mCRC patients enrolled in three large randomized tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
3
26
1
Order By: Relevance
“…2,4 Patterns similar to our current study were also seen for other acquired mutations in this study. 2,4 Furthermore, the study, using preclinical models, also revealed that extra-genomic transcriptomic mechanisms, specifically epithelial-to-mesenchymal transition, may explain cross-resistance between anti-EGFR-Ab and chemotherapy. 4 In summary, we maintain that these results indicate differing mechanisms of resistance to anti-EGFR-Ab used in combination with first-line chemotherapy and in later lines.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…2,4 Patterns similar to our current study were also seen for other acquired mutations in this study. 2,4 Furthermore, the study, using preclinical models, also revealed that extra-genomic transcriptomic mechanisms, specifically epithelial-to-mesenchymal transition, may explain cross-resistance between anti-EGFR-Ab and chemotherapy. 4 In summary, we maintain that these results indicate differing mechanisms of resistance to anti-EGFR-Ab used in combination with first-line chemotherapy and in later lines.…”
supporting
confidence: 90%
“…Additionally, and perhaps more importantly, these results are not isolated observation and are supported by similar findings from one of our other studies (Parseghian et al 4 ), which used data from large randomized trials comparing first-line and third-line anti–EGFR-Ab therapy. The rate of Acq-GAs seen was 9% versus 46% (our study: 7% v 62%) for the up-front use of anti-EGFR chemotherapy versus anti–EGFR-Ab therapy alone in studies with later lines.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The studies by Topham et al, 14 Raghav et al, 16 and Parseghian et al 17 reveal strikingly different molecular patterns of acquired resistance to anti-EGFR antibodies in colorectal cancer, with frequent heterogeneous genomic resistance mechanisms observed after late-line therapy but rarely observed after first-line therapy. These observations raise interesting questions about potential mechanistic differences in the emergence of acquired resistance between different lines of targeted therapy.…”
mentioning
confidence: 99%
“…Notably, even well-known anti-EGFR resistance mutations in KRAS and even EGFR-ECD-the latter not previously observed in the absence of prior anti-EGFR exposure-were observed at similar frequency between the cetuximab and bevacizumab arms after first-line therapy. This suggests a much different pattern of Finally, in a third study, Parseghian et al 17 directly compared paired pretreatment and postprogression plasma samples between patients receiving anti-EGFR antibody therapy in one first-line trial versus two third-line trials. Similarly, they observed the frequency of acquired genomic resistance alterations was substantially higher in the thirdline setting (46%) compared to the first line (9%).…”
mentioning
confidence: 99%